Transparency vs Privacy in Credit Markets - Yu Awaya; Hiroki Fukai; Makoto Watanabe (CESifo GmbH, 2024)
We compare Transparency and Privacy in credit markets. A long-lived borrower, who has a risky investment opportunity, seeks loans from a sequence of short-lived lenders. Under Transparency, all the information about the past investment outcomes is shared among the future lenders, which helps the lenders learn the borrower's type. In contrast, no information is shared under Privacy. We first show that under both Transparency and Privacy, the iterated elimination of dominated strategies leaves unique outcomes. We then show that trade stops earlier under Transparency than under Privacy. A higher social welfare is achieved under Privacy than under Transparency.
Keywords: C73; D83; G20; 330; credit market; transparency; privacy; strategic experimentation